A time-resolved numerical study of the vapor-liquid-solid growth kinetics describing the initial nucleation phase as well as pulsed deposition processes - Eisenhawer, Bjoern; Sivakov, Vladimir; Christiansen, Silke; Falk, Fritz (Nano Letters, 2013)
Today, the vapor-liquid-solid (VLS) growth mechanism is a common process for the metal catalyzed bottom-up growth of semiconductor nanowires (NWs). Nevertheless, most of the literature only is concerned with the steady-state NW growth which applies when the amount of material supplied is equal to the amount consumed by the NW growth at the same time. While this description is suitable for chemical vapor deposition (CVD) or electron beam evaporation (EBE) processes after the initial nucleation time, problems arise when pulsed growth processes like pulsed laser deposition (PLD) are used since in this case the steady state growth condition cannot be applied. Moreover, the initial phase of NW growth cannot be described with steady state growth conditions, either. In this work, we present a modeling approach for VLS NW growth based on numerical simulations, which is capable of describing the nucleation phase of the VLS growth process as well as a pulsed deposition process. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-07
Keywords: chemical vapor deposition; incubation time; Nanowires; non-steady state; nucleation; numerical simulation; pulsed deposition; vapor-liquid-solid